PSYCHOSOCIAL CARE FOR THE ELDERLY IN SOCIAL ISOLATION/COVID-19 - Adriano da Silva Rozendo (Psicologia em Estudo, 2023)
The COVID-19 pandemic drove a large population contingent in Brazil and worldwide into social isolation. As reported by the highest international health authorities, including the World Health Organization (WHO), the elderly people are part of the so-called ‘risk group’ for the disease. Thus, more rigor and care were required among elderly people, including social isolation. It is well known that, despite the undeniable importance of this action, elderly people in social isolation were more exposed to a series of illnesses, mainly related to psychic problems. The goal of this paper is to propose psychosocial care for the elderly in a situation of distress, or vulnerability due to social isolation. The ideas seek to induce memory, cognition and psychomotricity through narratives, artistic resources, Information, Communication Technologies and autobiographical objects, such as video calls, reading, listening to music, storytelling and recalling. In general, the proposed activities can be coordinated by professionals and family members and adapted according to the characteristics of each elderly person.